Effects of 20-year infancy-onset dietary counselling on cardiometabolic risk factors in the Special Turku Coronary Risk Factor Intervention Project (STRIP): 6-year post-intervention follow-up. (May 2020) - Pahkala, Katja; Laitinen, Tomi T; Niinikoski, Harri; Kartiosuo, Noora; Rovio, Suvi P; Lagström, Hanna; Loo, Britt-Marie; Salo, Pia; Jokinen, Eero; Magnussen, Costan G; Juonala, Markus; Simell, Olli; et al.
Summary: Background: Primordial and primary prevention is the cornerstone for cardiometabolic health. In the randomised, controlled Special Turku Coronary Risk Factor Intervention Project (STRIP; n=1116), a 20-year dietary counselling intervention was given to children biannually from infancy, and cardiometabolic health benefits had been observed among the participants in the intervention group. Here, we report on the key results of the first follow-up done 6 years after the end of the intervention, at age 26 years. Methods: The randomised controlled STRIP study recruited children at age 5 months from well-baby clinics in Turku, Finland, and randomly assigned them to either an intervention or control group; group allocation was unmasked. The intervention introduced participants to a heart-healthy diet, characterised by low proportional intake of saturated fat and cholesterol, by dietary counselling and nutrition education sessions to parents and children from the age of 7 months to 20 years. Children in the control group received only the basic health education given at Finnish well-baby clinics and school health care. We assessed diet, lifestyle, and cardiometabolic risk factor data, including blood pressure, anthropometry, serum biochemistry (lipids, apolipoproteins, glucose, and insulin), and homoeostatic model assessment of insulin resistance (HOMA-IR) in the participants at age 26 years. Findings: 1116 children were included in the original STRIP study, of whom 551 provided data at the age 26 years follow-up, and data for 507 participants were analysed (243 in the intervention group and 264 in the control group). At follow-up, those who had been in the intervention group had slightly lower mean intake of saturated fat as a proportion of total energy intake than the control group (13·0% [SD 3·3] vs 13·7% [3·6], p=0·049). A higher proportion of participants in the intervention group achieved the targeted monounsaturated and polyunsaturated fat to saturated fat ratio of more than 2:1 than the control group (78 [39%] of 200 vs 70 [30%] of 235; risk ratio [RR] 1·16 [95% CI 1·01–1·33]; p=0·035). A higher proportion of intervention group participants met the ideal total cholesterol concentration of less than 5·17 mmol/L (194 [81%] of 240 vs 187 [72%] of 261; RR 1·45 [1·05–2·01], p=0·024) and optimal LDL cholesterol concentration of less than 3·0 mmol/L (166 [69%] of 240 vs 158 [61%] of 251; RR 1·30 [1·03–1·66], p=0·031). Those who received the intervention had lower glucose (5·00 mmol/L [SD 0·43] vs 5·07 mmol/L [0·46], p=0·040) and HOMA-IR (median 1·44 [IQR 1·09–1·91] vs 1·62 [1·22–2·09], p=0·037) than the participants in the control group. Interpretation: Previously observed intervention effects during the 20-year counselling were largely maintained into adulthood 6 years after the withdrawal of the intervention. Dietary counselling introduced in infancy thus provided a sustained benefit to diet quality and cardiometabolic risk factor levels. Funding: Academy of Finland, Juho Vainio Foundation, Finnish Foundation for Cardiovascular Research, Finnish Ministry of Education and Culture, Finnish Cultural Foundation, Sigrid Jusélius Foundation, Special Governmental grants for Health Sciences Research (Turku University Hospital), Yrjö Jahnsson Foundation, Finnish Medical Foundation, and Turku University Foundation.